2018
DOI: 10.1177/1475921718808223
|View full text |Cite
|
Sign up to set email alerts
|

AR-glass/carbon-based textile-reinforced concrete elements for detecting water infiltration within cracked zones

Abstract: The study examines the use of hybrid carbon-based textile-reinforced concrete elements with self-sensing capabilities to quantitatively detect wetting events within cracked zones. The self-sensory structural element combines the advantages of AR-glass and carbon-based textile-reinforced concrete for thin-walled structural elements with those stemming from the electrical properties of reinforced carbon rovings. The article investigates the sensitivity of sensory carbon rovings to distinguish between the magnitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…It was found that this material could be a good candidate for monitoring stress state changes and, therefore, has the potential for use in this area. Alkali-resistant (AR)-glass and carbon-based textile-reinforced concrete, which was implemented in the experiment conducted by Goldfeld and Perry [ 105 ], was also found as a preferred material for leakage detection application. It was identified that hybrid carbon-based textile-reinforced concrete can detect and discern the magnitude of wetting, as well as determine the severity of the surface cracking.…”
Section: Applications Of Self-sensing Concretementioning
confidence: 99%
See 1 more Smart Citation
“…It was found that this material could be a good candidate for monitoring stress state changes and, therefore, has the potential for use in this area. Alkali-resistant (AR)-glass and carbon-based textile-reinforced concrete, which was implemented in the experiment conducted by Goldfeld and Perry [ 105 ], was also found as a preferred material for leakage detection application. It was identified that hybrid carbon-based textile-reinforced concrete can detect and discern the magnitude of wetting, as well as determine the severity of the surface cracking.…”
Section: Applications Of Self-sensing Concretementioning
confidence: 99%
“…A similar experimental pattern and material use was observed for weight in motion application [ 11 , 38 , 100 , 102 , 103 ]. In order to sense and detect leakage, the fillers dispersed inside the concrete and fiber-based textile reinforcement have been used [ 16 , 104 , 105 ]. Some researchers used embedded cement-based piezoelectric sensors for corrosion process monitoring [ 6 ].…”
Section: Applications Of Self-sensing Concretementioning
confidence: 99%
“…The high tensile strength of the rovings and their high resistance against corrosion enable the production of thin-walled and structurally strong TRC elements. The use of electrically conductive rovings, such as carbon rovings, that are characterized by high mechanical performance enables the rovings to serve both as the main reinforcement system as well as the sensory agent for detecting mechanical loading (Christner et al, 2012; Goldfeld et al, 2016a, 2017b; Wen and Chung, 1999; Wen et al, 2000), strain (Horoschenkoff and Christner, 2012; Quadflieg et al, 2016; Teomete, 2015), cracking (Goldfeld et al, 2017a; Goldfeld and Yosef, 2019); or water infiltration (Goldfeld and Perry, 2018, 2019; Goldfeld et al, 2016b, 2016c).…”
Section: Introductionmentioning
confidence: 99%
“…The sensory concept of the smart system to detect water leakage is based on the changes of electrical properties of two adjacent carbon rovings reinforcement due to infiltration of water through cracked zones, Goldfeld and Perry (2018, 2019). The sensory characterization of the carbon rovings to monitor water leakage is correlated to the unique micro-structural mechanism of the rovings within the cementitious matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation